A simplified model of the process of medical attention. Assistance, educational and investigative implications - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
The process of medical attention constitutes a learning object for the student of Medicine. In this article a simplified model is proposed or general of the process of medical attention whose employment possesses assistance, educational and investigative implications; elaborated on the base of the address of the mental activity that the doctor develops during the execution of the process. Starting from this idea we identify three moments or phases like components of the pattern: 1) the obtaining of information, 2) the interpretation of the information, and 3) the taking of decisions; each one of which possesses a specific objective in function of the general objective of the process, besides other particularities. The property of generality of the elaborated pattern is identified, as well as its limitations.